Removal of Hazardous Brilliant Cresyl Blue Dye Utilizing Aluminum Oxide as Photocatalyst - Hazim Yahya Al-Gubury; Hajir S. Alteemi; Ali Malik Saad; Rafal R. Al-Shamary (Indonesian Journal of Chemistry, 2019)
Photocatalytic degradation of brilliant cresyl blue stain has been done by irradiating the solution pigment with a solar light in presence of aluminum oxide. The effect of important reaction has included many parameters such as catalyst mass, the initial concentration of brilliant cresyl blue dye, the effect of temperature, and initial P has been investigated in a batch reactor. All experiments are determined by usage of UV-visible spectrophotometer analyzer. The optimal concentration of catalytic has observed at 0.17 g/100 cm3 while the typical concentration of stain was recorded at 50 mg/cm3. Photocatalytic break down of shining cresyl blue pigment was favorable in the Ph 10 and 8.44 mW/cm2 light intensity. This type of degradation of the present dye study has obeyed the pseudo-first-order reaction. Photocatalytic degradation of brilliant cresyl blue dye has studied by using various concentrations of aluminum oxide. This concentration was suspended in an aqueous solution of dye which has irradiated by solar radiation in a vessel reactor at room temperature with 10 cm3/min air bubble was passed through the solution.